The impact of threat of punishment on tax compliance and non-compliance attitudes in Malaysia - Mohd. Isa, Khadijah; Mohdali, Raihana; Yussof, Salwa Hana (2014)
Threat of punishment has been emphasized as one of the effective tools to deter taxpayers’ non-compliance attitudes. Thus this study aims to explore the impact of threat of punishment on both individual taxpayers’ attitudes, compliance and noncompliance. The findings from a mixed-modes survey indicate that threat of punishment is insignificant on taxpayers who are willing to comply with tax laws. They tend to avoid taxes when they are threatened with tax audits and penalties. Overall, threat of punishment appears to have not only an insignificant impact on compliant taxpayers but also trigger their intentions to be less compliant.